Theorising Male Virginity in Popular Romance Novels - Jonathan A. Allan (Journal of Popular Romance Studies, 2011)
Although the virginal female heroine is a standard trope in popular romance fiction, the male virgin in popular romance novels has yet to be studied or theorised. This study therefore seeks to explore and theorise the male virgin in heterosexual popular romance novels. Initially, I demonstrate at least four “types” of male virgins: the sickly virgin, the student virgin, the genius virgin, and the virgin as commodity. I conclude this theoretical groundwork by considering Eloisa James’ When the Duke Returns, which brings together each of these “types” of male virginity. Ultimately, I argue that male virginity in romance fiction is complex and is distinct from other treatments of male virginity in other popular media.